Analisis Faktor yang Mempengaruhi Kejadian Leukemia Limfoblastik Akut (LLA) pada Anak di RSUD Dr. Soetomo - Primadita Syahbani; Mia Ratwita Andarsini; Martono Tri Utomo; Siprianus Ugroseno Yudho Bintoro (Jurnal Kesehatan Masyarakat Indonesia, 2022)
Background: Childhood acute lymphoblastic leukemia (ALL) cases were in the first place in several Indonesia’s hospitals. The survival rate in Indonesia was low compared to other countries. Objective: To analyze the influencing factors of ALL among parental age, BW, cigarettes, hydrocarbons, and insecticides. Method: A matched case-control study involved children with malignancies at Dr. Soetomo General Hospital Surabaya on April 2019-June 2021. The cases were children with ALL and children with malignancies other than ALL as the control. The study included 55 people in each case and control group. Data were obtained from medical records and questionnaires. Result: Influencing factors of childhood ALL are paternal age <25 years old (OR=3; 95% CI=0,96–9,3), two types of hydrocarbon products (OR=0,23, 95% CI=0,065–0,8) and none (OR=3,33, 95% CI=1,33–8,30) maternal exposure of hydrocarbons, preconception exposure (OR=0,3; 95% CI=0,12–0,74), and none (OR=3,5; 95% CI=1,41–8,67) maternal period exposure to hydrocarbons. BW, cigarette exposure, and insecticides exposure are not the influencing factors. Using the multivariate analysis, no factors was found to be the most influential. Conclusion: Influencing factors of childhood ALL were paternal age <25 years, two types and none maternal exposure to hydrocarbons, preconception and none maternal period of hydrocarbon exposures